Significance of Crime Scene Visit by Forensic Pathologist in Cases of Atypical Firearm Injuries - Thejaswi, H.T.; Kumar, A.; Krishna, K. (Kathmandu University Medical Journal, 2017)
Deaths due to firearms are some of the interesting and contentious cases that a forensic pathologist/autopsy surgeon encounters in his practice. Whenever there is ‘ambiguity’ regarding the nature or sequence of events any unnatural deaths including those caused by firearms the practice of visiting crime scene should be encouraged especially in a country like India where autopsy surgeons often neglect it. Here we present a case report in which there were inconsistencies in the autopsy findings with the alleged history. The witnesses heard about four to six gunshot sounds, whereas only two spent cartridge cases were retrieved from the crime scene. Authors identified the atypical nature of firearm injuries sustained by the victims that were possible by just two bullets. Crime scene visit was undertaken where we discovered the possibility of the echo effect behind the production of four to six sounds. Further by using computer software program, positions of the gunman, victims and the bullet trajectory of the two bullets was created.